Case Studies of Public Sector Innovation in Increasing Local Tax Compliance - Pratiwi, Pratiwi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2019)
Public sector innovation (PSI) is important driving factor of economic development. Tax is one of the drivers of economic development as 70% of national expenditure are covered by tax revenue. However, the tax revenue ratio towards the Gross Domestic Product (GDP) in Indonesia is less than 13% and is the lowest among Southeast Asian economies. This study describes two case studies in local governments on increasing the awareness of the citizens to pay tax. This study focuses on innovation process, the knowledge flow, supporting conditions and challenges in implementing the innovations. By employing case study method, this study suggests acknowledgement, human resource training, multi-stakeholder partnership, and bottomp-up approach have stimulated innovativeness of public organizations.Â